Challenging the strategy paradigm within the paper packaging industry - Malin Olander Roese; Annika Olsson (International Journal of Business Science & Applied Management (IJBSAM), 2012)
Formulating and implementing a new strategy may be a challenging task, especially if it alters the way in which a company has operated and positioned itself before. This may be particularly true for companies within the forest industry, like manufacturers of paper packaging products, pursuing differentiated customer value and innovative solutions where, traditionally, success has been measured in volume and relative position on a cost curve. In theory there are different schools of thought and approaches on how to go about formulating and implementing strategy. In practice, going through strategic change may create a need to embrace new ways of thinking and acting in order to close the gap between formulation and implementation, between knowing what to do and doing it. This gap, particularly the interdependence between formulation and implementation in the context of change between strategies of different schools and assumptions, merits more attention in literature. The purpose of this paper is to contribute to the understanding of strategic change, illustrating a change process of formulating and implementing a strategy through the lenses of schools of strategy and cognitive research. The purpose is also to suggest areas for future research and practical guidance for organisations aiming to break away from a reigning strategy paradigm in search for new ways to compete. Based on a longitudinal case study of Billerud, a Swedish world-leading manufacturer of paper packaging material, two propositions are suggested for future research and practical guidance for managers when formulating and implementing strategic change. Firstly for an organisation going through strategic change, understanding the assumptions behind different strategic intents and the link between a chosen strategy and critical core activities, capabilities and culture is a prerequisite to enable a transition. Secondly, strategic change is enabled through an iterative and probing approach between formulation and implementation which considers knowledge and learning of new concepts, activity and culture as situated.
Keywords: 650; strategic change; strategy implementation; customer orientation; innovation; paper packaging industry